Photometric Study of the Globular Cluster System of M49 - Mahmoud-Perez, Aisha (My University, 2015)
This thesis presents deep photometry of the globular cluster system of the massive elliptical galaxy, M49. Using the C and T1 Washington filters from the MOSAIC camera on the Cerro Tololo Inter-American Observatory 4m telescope, we studied the color, metallicity and luminosity distributions of the globular cluster system. We find a strong bimodality in the color and metallicity distributions of the globular cluster system down to a magnitude of R <24, with 1718 clusters belonging to the blue population and 698 to the red population. In agreement with previous studies, the blue sequence does not exhibit a strong mass-metallicity relation. No difference is found in the mass-metallicity relation between the inner and outer clusters of M49. These results suggest that the mechanism responsible for the mass-metallicity re- lation is not local and may be affected by the galaxy’s individual dynamic history, location in the galaxy cluster and the formation of the globular cluster system itself. We suggest a mechanism based on accretion of gas by proto-clusters as they orbit within their parent dwarf galaxies. The latter would fit the observed behavior of the MMR.
Keywords: globular clusters, elliptical galaxies, astronomy, physics